Treatment With the CSF1R Antagonist GW2580, Sensitizes Microglia to Reactive Oxygen Species - Soto-Diaz, Katiria; Vailati-Riboni, Mario; Louie, Allison Y.; McKim, Daniel B.; Gaskins, H. Rex; Johnson, Rodney W.; Steelman, Andrew J. (Frontiers in Immunology, 2021)
Microglia activation and proliferation are hallmarks of many neurodegenerative conditions and may contribute to disease pathogenesis. Neurons actively regulate microglia survival and function, in part by secreting the microglia mitogen interleukin (IL)-34. Both IL-34 and the colony stimulating factor (CSF)-1 bind colony stimulating factor receptor (CSFR)1 on microglia. Systemic treatment with central nervous system (CNS) penetrant, CSFR1 antagonists, results in microglia elimination in a dose dependent matter, while others, such as GW2580, suppress activation during disease states without altering viability. However, it is not known how treatment with non-penetrant CSF1R antagonists, such as GW2580, affect the normal physiology of microglia. To determine how GW2580 affects microglia function, C57BL/6J mice were orally gavaged with vehicle or GW2580 (80mg/kg/d) for 8 days. Body weights and burrowing behavior were measured throughout the experiment. The effect of the GW2580 on circulating leukocyte populations, brain MG morphology, and the transcriptome of magnetically isolated adult brain microglia was determined. Body weights, burrowing behavior, and circulating leukocytes were not affected by treatment. Analysis of Iba-1 stained brain microglia indicated that GW2580 treatment morphology, but not number of cells. Analysis of RNA-sequencing data indicated that genes related to reactive oxygen species (ROS) regulation and survival were suppressed by treatment. Treatment of primary MG cultures with GW2580 caused a dose-dependent reduction in viability only when the cells were concurrently treated with LPS, an inducer of ROS. Pre-treatment with the ROS inhibitor, YCG063, blocked treatment induced reductions in viability. Finally, GW2580 sensitized MG to hydrogen peroxide induced cell death. Together, these data suggest that partial CSF1R antagonism may render microglia more susceptible to reactive oxygen and nitrogen species.